Life‐threatening oral mucositis following chemotherapy in a pediatric patient. Issue 6 (10th June 2021) - Tsuboi, Kaoru; Tsuboi, Norihiko; Sakamoto, Kenichi; Takebayashi, Akira; Tomizawa, Daisuke; Nishimura, Nao; Nakagawa, Satoshi
Abstract: Severe oral mucositis as a complication of chemotherapy may lead to airway obstruction and require prolonged intubation. As its course is consistent with the course of neutropenia, airway management strategies should be determined individually. Abstract : Severe oral mucositis as a complication of chemotherapy may lead to airway obstruction and require prolonged intubation. As its course is consistent with the course of neutropenia, airway management strategies should be determined individually. ​